2000
DOI: 10.1093/intqhc/12.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of demand and supply for regionalized injury services: a case study in Greece

Abstract: The extra demand created by injured tourists is reflected in the seasonality of admissions for injuries. The district hospital of Kerkyra cannot be considered as deficient in comparison to other district hospitals. Nevertheless, the suboptimal function of the hospital, with respect to injuries, is reflected in the high proportion of injured patients transferred when the injury occurs outside the full working schedule of the hospital. Patients with burns, bone fractures or dislocations and head injuries or conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…On one hand, seasonal increases in hospital admissions may be weather dependent [ 3 , 5 - 13 ]. On the other hand, in certain areas tourism may cause seasonal variation in health service utilization by temporarily increasing a population at risk during holiday seasons [ 14 ]. Whereas climate-dependent variations involve the local population of an area, vacation-induced increases in hospital admission rates may largely derive from nonlocal residents.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, seasonal increases in hospital admissions may be weather dependent [ 3 , 5 - 13 ]. On the other hand, in certain areas tourism may cause seasonal variation in health service utilization by temporarily increasing a population at risk during holiday seasons [ 14 ]. Whereas climate-dependent variations involve the local population of an area, vacation-induced increases in hospital admission rates may largely derive from nonlocal residents.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last several decades, different studies have been conducted on the impact of tourism on the healthcare system and especially on EDs [36]. Investigated the impact of tourism on emergency admission rates in orthopaedic health service areas in Switzerland and found that hospital admission rates were up to 4 times higher in winter than in other seasons, almost entirely due to tourist admissions [40]. Investigated the imbalance in demand and supply for injury admissions caused by tourism in the hospital of Kerkyra (Greece) and found that the extra demand generated by tourists was reflected in the seasonality of injury admissions.…”
Section: Introductionmentioning
confidence: 99%